Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1103/physrevb.97.115401
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity induced by interfacial coupling to magnons

Abstract: We consider a thin normal metal sandwiched between two ferromagnetic insulators. At the interfaces, the exchange coupling causes electrons within the metal to interact with magnons in the insulators. This electron-magnon interaction induces electron-electron interactions, which, in turn, can result in p-wave superconductivity. In the weak-coupling limit, we solve the gap equation numerically and estimate the critical temperature. In YIG-Au-YIG trilayers, superconductivity sets in at temperatures somewhere in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 43 publications
2
54
2
Order By: Relevance
“…The quantity σ in front of the electron operators on the second line is +1 for spin up and −1 for spin down. Fourier transforming the magnon and electron operators c iσ = 1 √ N k c kσ e −ik·r i then produces [13]…”
Section: B Diagonalization Of Subsystemsmentioning
confidence: 99%
“…The quantity σ in front of the electron operators on the second line is +1 for spin up and −1 for spin down. Fourier transforming the magnon and electron operators c iσ = 1 √ N k c kσ e −ik·r i then produces [13]…”
Section: B Diagonalization Of Subsystemsmentioning
confidence: 99%
“…These excitations are quasiparticles known as magnons. Theoretical predictions of electron-magnon interactions have shown that these can also induce effects such as superconductivity [1][2][3][4][5][6][7][8][9][10].Research interest in antiferromagnetic materials is surging [11,12]. This enthusiasm is due to the promising properties of antiferromagnets such as high resonance frequencies in the THz regime and a vanishing net magnetic moment.…”
mentioning
confidence: 99%
“…These excitations are quasiparticles known as magnons. Theoretical predictions of electron-magnon interactions have shown that these can also induce effects such as superconductivity [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…Here also it is important to note, as in the case without superconductivity, that Eqs. (16a)-(16c) and (17) are obtained assuming the continuous spectrum of three-dimensional wave vectors of the superconducting electrons, whereas for the electron-magnon heat conductance we include only a two-dimensional integral. As a result this overestimates G q−ph and underestimates the resulting crossover temperature.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The interfacial electron-magnon interaction strength can be quite large, and hence important for the thin film materials, as the recent work on superconductivity induced in a metal due to interfacial electron-magnon interaction [17], and spin transport across normal metal and ferromagnetic insulator [18,19] Pγ denotes the incident radiation power, which increases the electronic temperature by an amount ∆T from some initial temperature T dictated by the temperature of the baths. For a low and constant power Pγ , the magnitude of ∆T = Pγ /G tot th is dictated by the total heat conductance, G tot th , to the heat bath.…”
Section: Introductionmentioning
confidence: 99%